2021
DOI: 10.1108/tqm-11-2020-0275
|View full text |Cite
|
Sign up to set email alerts
|

Enabling factors for adopting sustainable, organic wine production

Abstract: PurposeThis study expands the debate on the reasons that wine producers adopt sustainable, organic wine production. It aims to ascertain the enabling factors facilitating behavioral intention regarding such an adoption and whether these factors can be combined in a conceptual, measurable model.Design/methodology/approachA sample of 157 Italian winery companies was used. Results were analyzed through the unified theory of acceptance and use of technology model, various quantitative methods and a multi-regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
1
13
2
Order By: Relevance
“…In this context, CSR is progressively gaining importance in the wine sector too (Barber et al , 2006; Cobelli et al , 2021). The discussion about this relevant topic in the field of wine is closely linked to the sustainability concept.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, CSR is progressively gaining importance in the wine sector too (Barber et al , 2006; Cobelli et al , 2021). The discussion about this relevant topic in the field of wine is closely linked to the sustainability concept.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, scholars have investigated the impact of CSR disclosure on consumer's decision-making process (Pradhan, 2018). Accordingly, websites should be considered a proper communication channel to reach consumers (Hollebeek et al , 2007; Yen, 2014; Cobelli et al , 2021). More specifically, online disclosure should support companies in enhancing consumers' involvement in corporate social responsibility practices, influencing consumers' purchasing behaviour (Barber et al , 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Extant studies have identified several factors that influence a consumer's wine selection (Chaney, 2000; Cobelli et al , 2021; Cobelli and Wilkinson, 2020; Hollebeek et al , 2007; Duhan et al , 2019; Lategan et al , 2017; Quintal et al , 2017). However, most of these studies have been conducted in countries where the wine market has already reached the mature stage.…”
Section: Introductionmentioning
confidence: 99%